C++ cookbook - Stephens, D. Ryan (O'Reilly, 2006)
Despite its highly adaptable and flexible nature, C++ is also one of the more complex programming languages to learn. Once mastered, however, it can help you organize and process information with amazing efficiency and quickness. The C++ Cookbook will make your path to mastery much shorter. This practical, problem-solving guide is ideal if you're an engineer, programmer, or researcher writing an application for one of the legions of platforms on which C++ runs. The algorithms provided in C++ Cookbook will jump-start your development by giving you some basic building blocks that you don't.